Asymmetric Effects of Government Spending : Does the Level of Real Interest Rates Matter? - Choi, Woon (IMF Working Papers; Working Paper ;, 2005)
This paper empirically explores how fiscal policy (represented by increases in government spending) has asymmetric effects on economic activity at different levels of real interest rates. It suggests that the effect of fiscal policy depends on the level of real rates, since the Ricardian effect is smaller at lower financing costs of fiscal policy. Using threshold regression models on U.S. data, the paper provides new evidence that expansionary government spending is more conducive to short-run growth when real rates are low. It also finds asymmetric effects on interest rates and inflation, and threshold effects associated with substitution between financing methods.